A Qualitative Study to Examine How Differences in Motivation Can Inform the Development of Targeted Physical Activity Interventions for African American Women - Sweeney, Allison M. (Eval Program Plann, 2019)
Self-Determination Theory proposes that some people are motivated to initiate physical activity by externally-controlled reasons (e.g., physical appearance, approval from others), whereas others feel compelled by more autonomous sources of motivation (e.g., enjoyment, personal importance). This study used qualitative methods to examine whether individual differences in autonomous motivation offers a useful framework for developing targeted intervention programs for African American women. Focus groups (k = 6) were conducted to examine how different levels of autonomous motivation for physical activity related to differences in physical activity barriers and facilitators among African American women (N = 31). Sessions were audiotaped, transcribed, and coded by independent raters (r = .70). QSR NVivo 11 was used to analyze data, and themes were identified separately for women with low, medium, or high autonomous motivation. Those with high autonomous motivation focused on themes of wanting novelty, excitement, and competition, whereas those with low autonomous motivation focused on themes of wanting instrumental support and financial incentives for increasing engagement in physical activity. Implications for developing physical activity intervention programs for African American women that are targeted toward differences in autonomous motivation are discussed.